2012
DOI: 10.1590/s1020-49892012001300001
|View full text |Cite
|
Sign up to set email alerts
|

Peru's national folic acid fortification program and its effect on neural tube defects in Lima

Abstract: Peruvian legislative requirements for folic acid fortification are below international (WHO) recommendations; birth prevalence of NTDs in Lima is higher than international benchmarks; and no decrease in NTDs following fortification of flour with folic acid (according to Peruvian national standards) was observed. As increasing the level of folic acid in flour remains the most sustainable way of preventing NTDs, it is recommended that Peru increase its folic acid fortification requirements to meet those recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Pooled analyses showed a strong association between folic acid fortification and the decreased prevalence of total NTDs (OR: 0.59; 95% CI: 0.49, 0.70) ( Figure 5 ) and NTD subtype, including spina bifida (OR: 0.66; 95% CI: 0.53, 0.82) ( Supplemental Figure 8 ), anencephaly (RR: 0.49; 95% CI: 0.40, 0.60) ( Supplemental Figure 9 ), and cephalocele (OR: 0.64; 95% CI: 0.47, 0.88) ( Supplemental Figure 10 ). A single study conducted in Peru (57) was, however, associated with an apparent increase in spina bifida following implementation of the national folic acid fortification program. Among WRA, folic acid fortification of flour was associated with a significant decline in the prevalence of folate deficiency (RR: 0.20; 95% CI: 0.15, 0.25) ( Supplemental Figure 11 ), as well as improvements in serum/plasma folate levels (SMD: 1.25; 95% CI: 0.50, 1.99) ( Supplemental Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pooled analyses showed a strong association between folic acid fortification and the decreased prevalence of total NTDs (OR: 0.59; 95% CI: 0.49, 0.70) ( Figure 5 ) and NTD subtype, including spina bifida (OR: 0.66; 95% CI: 0.53, 0.82) ( Supplemental Figure 8 ), anencephaly (RR: 0.49; 95% CI: 0.40, 0.60) ( Supplemental Figure 9 ), and cephalocele (OR: 0.64; 95% CI: 0.47, 0.88) ( Supplemental Figure 10 ). A single study conducted in Peru (57) was, however, associated with an apparent increase in spina bifida following implementation of the national folic acid fortification program. Among WRA, folic acid fortification of flour was associated with a significant decline in the prevalence of folate deficiency (RR: 0.20; 95% CI: 0.15, 0.25) ( Supplemental Figure 11 ), as well as improvements in serum/plasma folate levels (SMD: 1.25; 95% CI: 0.50, 1.99) ( Supplemental Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding was similar to the findings of other studies [ 4 , 7 ]. Moreover, many studies suggested that iron folate prevents/reduces the occurrence of certain types of CMs, for example, neural tube defects [ 5 , 12 , 28 – 33 ]. This indicates that few participants were aware that folic acid/iron folate protects from some CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, folic acid supplements are recommended before pregnancy. Implementation of food fortification has been associated with reduced neural tube defect prevalence in several countries (Mills and Signore, 2004; Ricks et al , 2012). Nevertheless, data from clinical trials, epidemiological studies and reported occurrences of sequential affected pregnancies in some individuals despite use of folic acid all show that a proportion of neural tube defects are unresponsive to folic acid (Wald et al ,1991; Blom et al , 2006; Mosley et al , 2009).…”
Section: Introductionmentioning
confidence: 99%